The Brilliance of Turgot – Part I - Rothbard, Murray N. (MISES: Interdisciplinary Journal of Philosophy, Law and Economics, 2015)
In this article, the author presents and discusses the importance of the thought of Anne-Robert-Jacques Turgot for the History of Economic Thought. He highlights Turgot’s intellectual brilliance, his defense of the market economy and of free trade, and his contributions to the theories of value, trade, prices, production and distribution.